Human steroid and oxysterol 7α‐hydroxylase CYP7B1: substrate specificity, azole binding and misfolding of clinically relevant mutants. (20th February 2014) - Yantsevich, Aleksei V.; Dichenko, Yaroslav V.; MacKenzie, Farrell; Mukha, Dmitry V.; Baranovsky, Alexander V.; Gilep, Andrei A.; Usanov, Sergey A.; Strushkevich, Natallia V.
<x xml:space="preserve">Abstract</x> Oxysterols and neurosteroids are important signaling molecules produced by monooxygenases of the cytochrome P450 family that realize their effect through nuclear receptors. CYP7B1 catalyzes the 6‐ or 7‐hydroxylation of both steroids and oxysterols and thus is involved in the metabolism of neurosteroids and bile acid synthesis, respectively. The dual physiological role of CYP7B1 is evidenced from different diseases, liver failure and progressive neuropathy, caused by enzyme malfunction. Here we present biochemical characterization of CYP7B1 at the molecular level to understand substrate specificity and susceptibility to azole drugs. Based on our experiments with purified enzyme, the requirements for CYP7B1 hydroxylation of steroid molecules are as follows: C5 hydrogen in the α‐configuration (or double bond at C5), a polar group at C17, a hydroxyl group at C3, and the absence of the hydroxyl group at C20–C24 in the C27‐sterol side chain. 21‐hydroxy‐pregnenolone was identified as a new substrate, and overall low activity toward pregnanes could be related to the increased potency of 7‐hydroxy derivatives produced by CYP7B1. Metabolic conversion (deactivation) of oxysterols by CYP7B1 in a reconstituted system proceeds via two sequential hydroxylations. Two mutations that are found in patients with diseases, Gly57Arg and Phe216Ser, result in apo‐P450 (devoid of heme) protein formation. Our CYP7B1 homology model provides a rationale for understanding clinical mutations and relatively broad substrate specificity for steroid hydroxylase.